As tessituras entre O Apanhador no Campo de Centeio e as intimações do imaginário para a (auto)formação humana - Colpo, Eliana Rita Mariotto (2012)
The present piece of work was developed within the Research Group on Imaginary, Education and Memory (GEPIEM), a Master s degree Graduation Program in Education, in the field of Writing Culture: languages and learning. It has the analysis of the literary work "The Catcher in the Rye" by J. D. Sallinger as its methodological direction, with the aim of seeking convergence from this "novel of formation" (Bildungsroman) for reflections in education .In particular, to look for its contributions, in the sense of the composition between studies and the imaginary (self) human formation. The analyzed work is considered as a powerful symbolic and ideological device for being able to transit between a teenager and his conflicts, sufferings and individual drives in affective, social, and cultural contexts and the wider reach of the society of the time - mid-XX century. The narrative of the main character and his relationships with family, school peers and friends has a timeless dimension, ie, that can belong to any time, and this, therefore, makes the work so contemporary. From the reading of the work we extract some symbolic cores grouped into four "mythemes" able to show the wealth and power of the "novel of formation" for (self) human training. The first mytheme: a human can (self) be formed between conflict and madness in search of the treasure inside. The second mytheme: a (self) formation can take place on a trip between escape and confrontation. The third mytheme: a (self) human formation occurs by initiation and transmigration. In the last and fourth mytheme: the fall into the abyss as act of living and (self) forming. Such mythemes were analyzed in the light of studies of imaginary, especially in its symbolic aspects, in order to relate and appreciate the importance of reading the "novel of formation" and the writings of other ways to raise life to the education of the human being. In a perception that values the felt and lived things, as well as the known and proven ones.